Developing Intellectual Capital Model for Energy Industry - Ahmadizad, Arman; Rastad, Seyyed Arman; Zonoubi, Mohammad Hossein; Ebrahimzadeh, Mohsen (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Intellectual capital is an important topic that has been viewed as one of the most value increase of company resources and key capitals in entrepreneurial development. This study aims to design a model for measuring intellectual capital. The previous models are reviewed and indicators for measuring are extracted. The population is 1104 managers and experts of 13 firms of Iran Transfo Company and 285 samples were selected randomly classified from companies. Data were collected by questionnaire, and we use structural equation modelling for the analysis. Our proposed intellectual capital model includes 5 aspects of human, structural, customer, the relational and systemic capital. All aspects have significant positive relationship with each other. Structural, relational and customer capital had the most intense relationships in the model and systemic and human capital were in fourth and fifth respectively. Keywords: Customer capital, human capital, intellectual capital, relational capital, structural capital